SIMULASI DAN ANALISA DINAMIKA REMOTELY OPERATED VEHICLE (ROV) - Hujjatul Anam; Joga Dharma Setiawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
ROV (Remotely Operated Vehicle) is a type of underwater robot that resembles a ship. The robot is controlled by a pilot who controls the remote control. In this ROV tether as a link robot using the device as a source of energy on the surface of the ocean, remote control and sensing display. This study starts from the stage of modeling the body of the ROV using SolidWorks 2012 to obtain the value of gravity and the buoyancy of the ROV. Construct equations of mathematical modeling with MATLAB SIMULINK to generate 3 DOF motion of the ROV. Creating a world in language VRML files using software V-Realm Builder 2.0 and connect it to the ROV dynamics conditions in MATLAB SIMULINK. Then simulation of the ROV using sl3d toolbox contained in MATLAB 2013b and dynamics analysis of the ROV vision of ROV thruster force is modeled as the input plots generated Signal Builder with position and velocity with respect to time.